Non-destructive testing of metallic specimens - Tan, Liang Tee (2015)
In this report, there are two main topics that made up of this project. At the beginning, the contents of this report are regarding the various methods to analyze the welded metallic specimen’s surface defect. The insight of various non-destructive testing such as visual testing, magnetic particles testing, penetrant, radiography and ultrasonic testing were also discussed in the report. At the later stage of this report, the design and development of the phased array ultrasonic testing equipment was in the report. The necessary data, information and analyses required to automate the process for the phased array equipment were collected through the student and professor effort. The flow charts were also created for an easy understanding of how the process works and act as input information for the programmers to create software for the phased array equipment.